The Influence of Digital Marketing Tools on Consumer Purchase Intentions: A Case Study of Electronic City Jakarta - Tenata, Albert; Ruslim, Tommy Setiawan (STIE AMKOP, 2024)
Introduction/Main Objectives: Digital transformation has become a critical factor in global business competition, particularly in the B2B sector. This study examines the influence of digital marketing tools on consumer purchase intentions, focusing on Electronic City, a major electronic retail company in Jakarta facing sales challenges in the evolving digital marketplace. Background Problems: How do search engine advertising, content marketing, social media, and email marketing impact consumer purchase intentions in the electronic retail sector?. Novelty: Unlike previous studies with inconsistent findings, particularly regarding the impact of search engine advertising, social media, and email marketing, this study provides a focused and localized investigation into the impact of digital marketing strategies on purchase intent, narrowing the scope to specific digital marketing tools. Research Methods: The study employs a quantitative causal design using a purposive sampling method. A survey questionnaire with a Likert scale was distributed to 198 Electronic City consumers in Jakarta, aged 18 and above. Data was analyzed using SmartPLS 4.0 to test the proposed hypotheses. Finding/Results: All examined digital marketing tools (search engine advertising, email marketing, social media, and content marketing) demonstrated a positive and significant influence on purchase intention. Search engine advertising showed the strongest impact, followed by email marketing, social media, and content marketing. Conclusion: The research concludes that digital marketing strategies significantly shape consumer purchase intentions. For Electronic City, this means leveraging targeted search ads, personalized email communications, engaging social media content, and informative marketing materials can effectively drive consumer behavior and potentially mitigate sales challenges.